Morphology and Possible Clinical Significance of the Radiating Extraforaminal Ligaments at the L1-L5 Levels. Issue 18 (15th September 2017) - Zhong, Enyi; Zhao, Qinghao; Shi, Benchao; Zheng, Xuefeng; Zhao, Qinghui; Tan, Jinchuan; Ding, Zihai; Huang, Wenhua
Abstract : Study Design: A dissection-based study of 10 fresh-frozen human cadavers. Objective: The objective of this study was to identify and describe the radiating extraforaminal ligaments in the exit regions of the L1-L5 intervertebral foramina and to research their possible clinical significance. Summary of Background Data: The transforaminal ligaments at the L1-L5 intervertebral foramina have been well studied. However, detailed descriptions of the radiating extraforaminal ligaments at L1-L5 are lacking. Methods: Eighty L1-L5 intervertebral foramina from 10 fresh cadavers were studied, and the extraforaminal ligaments were identified. The quantity, morphology, origin, insertion, and spatial orientation of the extraforaminal ligaments in the L1-L5 regions were examined. The length, width, diameter, and thickness of the ligaments were measured using a vernier caliper. Results: A total of 224 extraforaminal ligaments were identified in the 80 L1-L5 intervertebral foramina, and the occurrence rate of extraforaminal ligaments was 100%. One hundred and eighteen (52.68%) of the extraforaminal ligaments were radiating ligaments, and 106 (47.32%) of the extraforaminal ligaments were transforaminal ligaments. There were 97 (43.30%) ligaments at the superior aspect of the exit regions of the intervertebral foramina, 51 (22.77%) ligaments at the anterior aspect, 44 (19.64%) ligaments at the inferior aspect, and 32 (14.29%) ligaments at the posterior aspect. The morphologies of the extraforaminal ligaments were divided into two types: the strap type and the trabs type. Conclusion: Radiating extraforaminal ligaments exist between spinal nerves and nearby structures. Radiating extraforaminal ligaments may be of clinical importance to surgeons. Dissecting the radiating extraforaminal ligaments before percutaneous endoscopic lumbar discectomy may be an important step in reducing postoperative pain, which may result in significant benefits for patients. Level of Evidence: 3